2015
DOI: 10.2105/ajph.2015.302637
|View full text |Cite
|
Sign up to set email alerts
|

Using Evidence-Based Policy, Systems, and Environmental Strategies to Increase Access to Healthy Food and Opportunities for Physical Activity Among Asian Americans, Native Hawaiians, and Pacific Islanders

Abstract: Recent initiatives have focused on the dissemination of evidence-based policy, systems, and environmental (EBPSE) strategies to reduce health disparities. Targeted, community-level efforts are needed to supplement these approaches for comparable results among Asian Americans and Native Hawaiians and Pacific Islanders (NHPIs).The STRIVE Project funded 15 Asian American and NHPI community-based organizations (CBOs) to implement culturally adapted strategies. Partners reached more than 1.4 million people at a cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Participants provided suggestions for outreach efforts tailored to their communities, an approach used in other studies. 35,36 The subthemes and community-specific recommendations were organized according to each level of the SEM framework to address barriers most pertinent to each respective community. Table 2 summarizes these community-specific recommendations for future efforts, reinforcing the main point of our findings: Barriers to CalFresh participation occur at multiple levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants provided suggestions for outreach efforts tailored to their communities, an approach used in other studies. 35,36 The subthemes and community-specific recommendations were organized according to each level of the SEM framework to address barriers most pertinent to each respective community. Table 2 summarizes these community-specific recommendations for future efforts, reinforcing the main point of our findings: Barriers to CalFresh participation occur at multiple levels.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted and culturally adapted interventions have been shown to be effectively implemented at the community level through CBOs. 35 In addition to CBOs, partnerships with the Department of Public Health, faith-based organizations, and community liaisons can greatly reduce stigma and promote participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, being insufficiently active, defined as less than 150 minutes of aerobic Interdisciplinary health professionals can work together to identify potential barriers limiting physical activity engagement (e.g., transportation, limited time, and lack of resources). Previous studies have identified that barriers such as mistrust and lack of support may discourage racial and ethnic minorities from participating in various research and healthrelated interventions (George et al, 2014;Patel et al, 2015). During the coronavirus disease 2019 (COVID-19) pandemic, physical activity programs are being creative.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Further our group, the New York University Center for the Study of Asian American Health (NYU CSAAH) has demonstrated that health promoting activities are feasible, acceptable, and sustainable by immigrant-serving CBO leadership and members. [14][15][16][17][18] For these reasons, CBOs are ideally situated to play an essential role in dementia care by providing education, addressing social needs, and creating a supportive environment for diverse adults.…”
Section: Introducing Defining and Refining The Role Of Community Organizationsmentioning
confidence: 99%